Managing Carbon Footprint at Music Festivals: A Study at Glastonbury Festival - Larasti, Anindya Kenyo (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2022)
The Glastonbury Festival, renowned as one of the greatest music festivals globally, has come under environmental scrutiny due to its substantial expansion. While the festival undeniably benefits the economy, it also has adverse effects by contributing to the carbon footprint. This phenomenon is a result of congregating a large number of individuals in a single location concurrently for an extended period of time. The carbon footprint generated is substantial, and when combined with the garbage generated, it can result in significant environmental harm. Recognizing this concern, the organizer has implemented a comprehensive strategy to reduce and control its carbon emissions. Hence, this study evaluated the efficacy of various approaches by employing the framework of energy consumption, trash generation, and transportation emissions (Fredline et al., 2005). The outcome demonstrates that Glastonbury Festival's endeavor to achieve environmental sustainability underscores its dedication to diminishing its carbon emissions while safeguarding its core identity. Glastonbury has implemented novel energy solutions, such as solar and wind power, biodiesel, and recycled vegetable oil waste, to reduce emissions and include sustainable energy sources. Furthermore, waste management has effectively diminished the usage of disposable plastic bottles, decreased trash through recycling efforts, and promoted the practice of participants taking their possessions with them. Lastly, the transportation emissions, which account for the largest proportion of the total emissions, still require a solution, since they remain the primary concern of the event. The Glastonbury Festival's sustainability could be improved by the implementation of additional measures, educational initiatives, and partnerships with environmental organizations.